3D conformal radiotherapy combined with transcatheter arterial chemoembolization for hepatocellular carcinoma - Zou, Li-Qun (World J Gastroenterol, 2014)
AIM: To compare transcatheter arterial chemoembolization (TACE) and 3D conformal radiotherapy (3D-CRT) with TACE monotherapy in hepatocellular carcinoma (HCC). METHODS: We searched all the eligible studies from the Cochrane Library, PubMed, Medline, Embase, and CNKI. The meta-analysis was performed to assess the survival benefit, tumor response, and the decline in α-fetoprotein (AFP) level. According to the heterogeneity of the studies, pooled OR with 95%CI were calculated using the fixed-effects or random-effects model. An observed OR > 1 indicated that the addition of 3D-CRT to TACE offered survival benefits to patients that could be considered statistically significant. Statistical analyses were performed using Review Manager Software. RESULTS: Ten studies met the criteria to perform a meta-analysis including 908 HCC participants, with 400 patients in the TACE/3D-CRT combination group and 508 in the TACE alone group. TACE combined with 3D-CRT significantly improved 1-, 2- and 3-year overall survival compared with TACE monotherapy (OR = 1.87, 95%CI: 1.37-2.55, P < 0.0001), (OR = 2.38, 95%CI: 1.78-3.17, P < 0.00001) and (OR = 2.97, 95%CI: 2.10-4.21, P < 0.00001). In addition, TACE plus 3D-CRT was associated with a higher tumor response (complete remission and partial remission) (OR = 3.81; 95%CI: 2.70-5.37; P < 0.00001), and decline rates of AFP level (OR = 3.24, 95%CI: 2.09-5.02, P < 0.00001). CONCLUSION: This meta-analysis demonstrated that TACE combined with 3D-CRT was better than TACE monotherapy for patients with HCC, which needs to be confirmed by large multicenter trials．